Pollen morphology of the tribe Inuleae (Compositae) in Thailand - Pornponggrungrueng, Pimwadee; Chantaranothai, Pranom (Thai Forest Bulletin (Botany), 2014)
Pollen of 17 species belonging to four genera of the tribe lnuleae (Compositae) in Thai land was studies by means of LM and SEM. The pollen grains are monad, radially symmetri cal, isopolar, subspheroidal and echinate. Features regarded as distinctive include size, spine rows and spine length. Two pollen groups based on a number of spine rows between ap ertures arc established: Group J has one genus, Anisopappus. and Group II has 3 genera, Blumea, Duhaldea and Pentanema, with 5 and 3-4 spine rows, respectively.